Comparative Study of Cervical Pap Smear and Visual Inspection of The Cervix To Detect Premalignant Disease of The Cervix - Khalil, Rozhan Yassin; Abdolrahman Qader, Khanda (Kurdistan Journal of Applied Research, 2020)
The goal of current study is to compare visual inspection method of the cervix by using acetic acid sensitivity, specificity, positive and negative predictive values with Pap smear test values. This cross sectional study was obtained in Sulaimani city Kurdistan region at Maternity Teaching Hospital throughout the period (first September 2012) to (first February 2001). This study include 115 samples were reproductive women and premenopausal between ages 20-50 years old with symptomatic women ( vaginal discharge, dyspareunia, post coital bleeding , intermenestrual bleeding ) and prepared patients for a Pap smear test done for them. The cervix was painted with 5% concentration of acetic fluid for visual inspection method and monitored for aceto-white wounds and biopsies were taken from suspected areas. After that, the samples in 95% concentration of the ethyl alcohol were fixed. The results shows that, 114 samples among all other samples were appropriate for analyzing, statistical data analyzed by Epi Info software program and Chi-squared test used to find significance between variables with considering P-value less or lower than 0.05 as significant level. The result indicate that sensitivity rate was 16% for visual inspection method, specificity 71%, positive predictive value 3.13% and negative predictive value 93.9% to detect pre-cancerous lesion of the cervix. In conclusion, cervix visual inspection method for cancer had a low rate sensitivity compare with pap smear with a non-significant relationship between the two methods and Pap smear needed to conform visual inspection for cervical cancer.